Qualitative exploration the end user context of BCC materials on COVID-19 guidelines and handwashing - Shatil, Tanvir; Afrin, Sonia; Saha, Swagatam; Ghosh, Dipanwita; Kamruzzaman, Md. (BRAC Institute of Governance and Development (BIGD), 2022)
As a partner of the “Hygiene and Behaviour Change Coalition (HBCC),” BRAC Institute of Governance and Development (BIGD) initiated a rapid formative research to identify gaps in people’s existing hygiene knowledge and practice, as well as opportunities for intervention. In doing so, the study aimed to help BRAC design and develop new Behavioral Change and Communication (BCC) materials that can effectively address people’s particular hygiene behaviour during the COVID-19 pandemic. The two specific objectives of this study included investigating how users perceive the awareness messages and translate them into their everyday behaviour, and finding out the facilitating factors and the barriers they face in following Coronavirus-related public health and social guidelines. We selected 30 different respondents from Dhaka and Khulna and conducted in-depth telephone interviews, online focus group discussions (FGDs) through video conferencing, and shadow and visual content observation (e.g. photographs and videos). It was revealed that respondents have different levels of knowledge and practices including correct, partially correct and misconception on three domains: hand washing, mask use and social distancing. The study also revealed the personal and structural barriers to comply with the guidelines.